Effective two-body model for spectra of clusters of H 2, H 3, He 3, and He 4 with He 4, and H 2 - He 4 scattering - Fraser, P.; Massen-Hane, K.; Kadyrov, A.; Amos, K.; Bray, Igor; Canton, L. (The American Physical Society, 2017)
© 2017 American Physical Society. Four light-mass nuclei are considered by an effective two-body clusterization method: Li7 as H3+He4,Be7 as He3+He4,Be8 as He4+He4, and Li6 as H2+He4. The low-energy spectra of the first three are determined from single-channel Lippmann-Schwinger equations. For the last, two uncoupled sets of equations are considered: those involving the S31 and those of the posited 1S0 states of H2. Low-energy elastic scattering cross sections are calculated from the same H2+He4 Hamiltonian, for many angles and energies for which data are available. While some of these systems may be more fully described by many-body theories, this work establishes that a large amount of data may be explained by these two-body clusterizations.